Дифференциация социального пространства Украины и Беларуси как эффект "столкновения цивилизаций" - Кандрычын, С. (Социология: теория, методы, маркетинг, 2008)
The purpose of given comparative-regional analysis is to identify and to describe the steady social and mental structures, based on the mechanisms of longue durée (F.Brau del) functioning in the historical boundaries of civilization areals. The other relevant in this discussion framemork approach is based upon P.Bourdieu’s con clusions about creative features of social space. he East-West social space differentiation on the territory of Ukraine and Belarus may be considered as a result of historical interaction between two different civilizations: the European that has been spread its influence from the West and the Russian Orthodox advanced from the East. Our findings show that manifestation of the East-West spatial polarity appears to be associated with historical changes occurred in Eastern Europe during the second half of the 20th century. The paper analyzes a scope of social, demographic and cultural differentiation with regard to historical division of both countries in this context. The main groups of regional variables/indices, such as: socio-political (electoral preferences, religious practices etc.), socio-demographic (divorces, extramarital child ren), medical-social (i.e. social illnesses: tuberculosis, syphilis, AIDS etc.) are copared. The results indicate at a statistically meaningful polarity between both countries’ Eastern and Western regions in these characteristics distribution, while the Central region take up an intermediate position. So, our analyzes provides evidence of long historical frames existence determining specific regional characteristics transmitted across generations.